Multifocal Extranodal Involvement of Diffuse Large B-Cell Lymphoma - Cabuk, Devrim (Hindawi Publishing Corporation, 2013)
Endobronchial involvement of extrapulmonary malignant tumors is uncommon and mostly associated with breast, kidney, colon, and rectum carcinomas. A 68-year-old male with a prior diagnosis of colon non-Hodgkin lymphoma (NHL) was admitted to the hospital with a complaint of cough, sputum, and dyspnea. The chest radiograph showed right hilar enlargement and opacity at the right middle zone suggestive of a mass lesion. Computed tomography of thorax revealed a right-sided mass lesion extending to thoracic wall with the destruction of the third and the fourth ribs and a right hilar mass lesion. Fiberoptic bronchoscopy was performed in order to evaluate endobronchial involvement and showed stenosis with mucosal tumor infiltration in right upper lobe bronchus. The pathological examination of bronchoscopic biopsy specimen reported diffuse large B-cell lymphoma and the patient was accepted as the endobronchial recurrence of sigmoid colon NHL. The patient is still under treatment of R-ICE (rituximab-ifosfamide-carboplatin-etoposide) chemotherapy and partial regression of pulmonary lesions was noted after 3 courses of treatment.